Monitoring cases of pyrethroid intoxications in cats in Tirana region, Albania during 2016-2020 - Mavromati, J; Mehmedi, B (Journal of the Hellenic Veterinary Medical Society, 2023)
Pyrethroids are synthetic insecticides which are being widely used to control fleas and ticks in house hold pets. However, their use extends to pest control as well. Products used worldwide to protect pets are in liquid form and comprise spot-ons, shampoos, and spray. Close attention should be paid to proper usage of such insecticides in pets, particularly in cats. As already indicated by many studies, accidental or improper usage of such products can trigger severe health problems even proving fatal in cats. The objective of the current paper is to undertake a retro spective study of a total number of 47 cases suffering from pyrethroid intoxication in cats across several clinics in Tirana, Albania during the period 2016-2020. Records from the veterinary clinics were closely scrutinized with only specific cases of pyrethroid intoxication being included for the purposes of this study. The main clinical signs which were noticed in 47 cats included symptoms such as tremor/muscle fasciculation (37 cats; 76.6%), seizures (18; 38.3%), hyperaesthesia (19; 40.43%), ptyalism (13; 27.66%), ataxia (11; 23.4%), mydriasis (10; 21.28%). Out of 47 cases, 7 or 14.9 % of the treated cats did not survive. The outcome was solid after rapid interventions in 31 (65.96%) cats with the exception of 2 cats which did not survive dispide receiving treatment. Whereas as many as 16 (34.04%) of cats, having being taken late to the clinics, survived upon receiving treatment, while as few as 5 cats (31.25%) died. Awareness campaign targeting pet owners, owner education, appropriate product labelling and consultations with veterinarians may help eliminate this problem in the future.